Don Walsh, Shirley Walsh, Des Walsh, Charlie Walsh, Monica Walsh and Vince Walsh in Jerseyside around the late sixties (1950)
Christmas at the house in Jerseyside, Placentia. Individuals photographed, if any, have been identified within the title from left to right.